Bacterioplancton de tres humedales altoandinos de la cordillera Oriental de Colombia (2015)
Planktonic bacteria are involved in the process of recycling energy and take part in the bio-geochemical cycles of carbon, nitrogen and phosphorus by the processes of mineralization and transformation from inorganic compounds to organic matter. Thus these compounds are available in higher trophic levels. Although we know the importance of these bacteria, the knowledge is still low about the processes particularly how are organized in the Andes trop-ical ecosystems. The aim of this study was to carry out the characterization of planktonic bacteria: biomass, abundance and morphology in the Andean wetlands of the Eastern Cordillera. Triplicate samples were taken from surface, deep and littoral water from three lakes (La Cristalina, Laguna Negra, and Laguna Verde) in Boyacá. We found low abundance and biomass but these are within the range for oligotrophic lakes. The bacillary forms were most common in these ecosystems. Variations in abundance were found in relation to the season, being higher during the dry season.